Development of the AgWise forecast-based Optimum Planting Date and Cultivar Advisory Framework - Ahmed, Jemal Seid; Aguilar Ariza, Andres; Degefie, Degefie Tibebe; Louise Leroux; Mkuhlani, Siyabusa; Worku, Wuletawu Abera; Llanos Herrera, Lizeth; Ramirez Villegas, Julian Armando; Ghosh, Aniruddha (2025)
AgWise delivers tangible impact from climate science investments, transforming ensemble forecasts and data innovations into actionable advisories that directly improve planting decisions, productivity, and resilience for smallholder farmers. It operationalizes the forecast-based action, bridging the gap between global climate intelligence and local agricultural services- enabling governments and partners to act early, plan better, and manage risk more efficiently. Tested across Ethiopia, Kenya, Zambia, and Rwanda, AgWise has demonstrated scalability, cost-effectiveness, and adaptability to diverse agro-ecological and data contexts, positioning it for national and regional integration under ongoing climate service initiatives. By converting climate information into livelihood decisions, AgWise strengthens food security systems, advances the CGIAR and AICCRA goals on digital innovation and resilience, and demonstrates clear value for money and long-term sustainability for donor investment.